2016
DOI: 10.1080/17522439.2016.1229361
|View full text |Cite
|
Sign up to set email alerts
|

What predicts stigmatisation about schizophrenia? Results from a general population survey examining its underlying cognitive, affective and behavioural factors

Abstract: Stigmatisation towards individuals diagnosed with schizophrenia (SZ individuals) remains an important problem, yet few studies to date have examined a theoretically comprehensive set of predictors of stigmatisation. This study aimed to evaluate cognitive, emotional and behavioural aspects of stigmatisation towards SZ individuals in the Belgian general population in order to better understand its underlying factors. A sample of 544 participants completed online questionnaires assessing common stereotypes regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…This means that participants without schizophrenia would not 'mask' negative opinions towards people with schizophrenia when answering in their own name, suggesting that stigmatizing opinions on schizophrenia are not counter-normative. Moreover, previous international research has shown that the public also endorses ideas and emotions relative to pity and empathy concerning the suffering of people with schizophrenia (Thonon and Larøi, 2017). However, reference to this was rather absent from the answers of participants without schizophrenia, which could be interpreted in terms of stigma and the lack of "social" recognition of this suffering.…”
Section: Discussionmentioning
confidence: 91%
“…This means that participants without schizophrenia would not 'mask' negative opinions towards people with schizophrenia when answering in their own name, suggesting that stigmatizing opinions on schizophrenia are not counter-normative. Moreover, previous international research has shown that the public also endorses ideas and emotions relative to pity and empathy concerning the suffering of people with schizophrenia (Thonon and Larøi, 2017). However, reference to this was rather absent from the answers of participants without schizophrenia, which could be interpreted in terms of stigma and the lack of "social" recognition of this suffering.…”
Section: Discussionmentioning
confidence: 91%
“…For example, an online study of attitudes toward mental illness found that one-third of the sample would distance themselves from someone with schizophrenia and a full 20% would "flee" if in contact with a person with schizophrenia. 79 These responses were attributed to fear of unpredictability and perceived dangerousness. Importantly, little is known about the temporal relation between behaviors associated with the illness, social distancing and rejection, and social disability.…”
Section: What Is the Role Of Stigma And Rejection For Social Disconnementioning
confidence: 99%
“…On retrouve partiellement ces résultats en population générale belge francophone, où les facteurs les plus fréquents sont « l'imprévisibilité » et le « faible pronostic », mais la « dangerosité » est plus rare. En revanche, ce sont bien la « dangerosité » et l'« incompétence » qui sont les facteurs les plus associés à la peur et aux réactions d'évitement 11 .…”
Section: Le Stéréotype Associé à La Schizophrénie : Spécificitésunclassified